The Management Consultant: Mastering the Art of Consultancy (Financial Times Series) - Newton, Richard (Financial Times, 2012)
"The secret for success in attracting, winning, retaining and growing client business whether working as an independent or for a firm." Mike Lander, CEO, Consulting Strategies Ltd "Richard knows what clients value and provides clear, practical and experienced guidance on how to become and more importantly, be recognised and selected as the best."